2016
DOI: 10.21608/ejss.2016.347
|View full text |Cite
|
Sign up to set email alerts
|

Quality Parameter and Chemical Composition of Spinash Plant as Affected by Mineral Fertilization and Selenite Foliar Application

Abstract: FIELD experiment was carried out at the Experimental Farm of the Faculty of Agric., El-Mansoura Univ. during season 2015, arranged in split block design with 3 replicates to evaluate the effect of 3 rates of NPK treatments (50, 100 and 150 % from recommended dose) as main plots and 4 levels of sodium selenite in a foliar way (0, 10, 20 and 30 mg kg-1) as sub plots. Results indicated that NPK fertilization up to 100 % under study significantly increased the average values of chlorophyll, fresh and dry weight, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…For the shoot vitamin C content, only the treatment with 10 ppm Se resulted in a significant increasing in the 1 st season, while an increasing were observed in both treatments of 10 ppm Se and 100 ppm Mo in the 2 nd season (Table 4 and 5). Such results were supported by the finding of Fouda (2016), who reported that the foliar application of Se caused a significant increase of vitamin C in spinach plants.…”
Section: The Contents Of Chlorophyll Vitamin C and Protein In The Edsupporting
confidence: 78%
See 3 more Smart Citations
“…For the shoot vitamin C content, only the treatment with 10 ppm Se resulted in a significant increasing in the 1 st season, while an increasing were observed in both treatments of 10 ppm Se and 100 ppm Mo in the 2 nd season (Table 4 and 5). Such results were supported by the finding of Fouda (2016), who reported that the foliar application of Se caused a significant increase of vitamin C in spinach plants.…”
Section: The Contents Of Chlorophyll Vitamin C and Protein In The Edsupporting
confidence: 78%
“…Also, Se as a trace mineral was shown to affect multiple physiological and biochemical processes in different plant species (Moussa et al 2010). In previous studies, it has been observed that foliar application of Se increased the plant growth and yield in lettuce (Simojoki, 2003) and spinach (Fouda, 2016). Several studies reported that Mo nutrition enhances the growth and yield of leafy vegetables comparing with Mo deficiency conditions (Kaiser et al 2005;Moncada et al 2018).…”
Section: Growth Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorous promotes healthy root growth. Phosphorous also has vital importance in increase plant height, better root, development and also improve the yield of Indian spinach [5]. Potassium activates plant physiology, improves fruit quality, increase disease resistance, prevents lodging and makes the plant capable of surviving moisture stress.…”
Section: Introductionmentioning
confidence: 99%